From the nation state to Europe : essays in honour of Jack Hayward - Hayward, Jack Ernest Shalom; Menon, Anand, 1965-; Wright, Vincent (Oxford University Press, 2001)
The relationship between the European Union and its member states is complex and evolving. This book explores not only the nature of this relationship, but also the broader implications of European integration for the ways in which the subject of European politics is studied.
Keywords: European Union.; European Union; European Union countries -- Politics and government.; European Union countries -- Economic policy.; European Economic Community countries -- Economic policy.; Pays de l'Union européenne -- Politique économique.; LAW -- International.; Economic policy; Politics and government; European Union countries